2012
DOI: 10.1136/annrheumdis-2011-200801
|View full text |Cite
|
Sign up to set email alerts
|

Patient and provider barriers to effective management of gout in general practice: a qualitative study: Figure 1

Abstract: There are widespread misconceptions and lack of knowledge among both patients and health professionals concerning the nature of gout and its recommended management, which leads to suboptimal care of the most common inflammatory joint disease and the only one for which we have 'curative' treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
156
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(179 citation statements)
references
References 34 publications
10
156
0
7
Order By: Relevance
“…Furthermore, the predominantly male patients may feel that they have to appear 'manly' and bear with the symptoms. (14) Adherence rates to pharmacotherapy in gout are particularly poor, ranging from 18%-44%, and significantly lower than those in patients with other chronic diseases. (15,16) Reasons offered by patients who were nonadherent include the belief that they were cured, fear of side effects and pill burden; (14) this is especially relevant in the local context as most formulations of allopurinol are only available in 100-mg tablets.…”
Section: Patient Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the predominantly male patients may feel that they have to appear 'manly' and bear with the symptoms. (14) Adherence rates to pharmacotherapy in gout are particularly poor, ranging from 18%-44%, and significantly lower than those in patients with other chronic diseases. (15,16) Reasons offered by patients who were nonadherent include the belief that they were cured, fear of side effects and pill burden; (14) this is especially relevant in the local context as most formulations of allopurinol are only available in 100-mg tablets.…”
Section: Patient Factorsmentioning
confidence: 99%
“…Studies among health professionals have shown that many perceive gout as an acute disease and presume that patients would prefer to take painkillers when necessary rather than be on long-term medication. (14) In a healthcare system such as Singapore's where patients tend to visit a variety of doctors and hospitals, there may be inertia to start a new drug unless the patient sees the same doctor who can appreciate their recurrent attacks.…”
Section: Physician Factorsmentioning
confidence: 99%
“…36,37 It is no longer appropriate to consider gout as the 'disease of the affluent' or that it is solely related to overindulgence. …”
Section: Resultsmentioning
confidence: 99%
“…Highly effective uric acid-lowering therapies (ULTs) are available, however, adherence to ULTs in gout patients is among the lowest of all chronic diseases [11]. Poor quality educational resources and limited patient knowledge have been identified as key barriers to adequate ULT adherence [12,13]. Delivery of an intervention by nurses comprising of personalised education, lifestyle advice and appropriate prescribing of ULTs resulted in 92% of patients achieving target SUA concentrations oneyear post-intervention [14].…”
Section: Introductionmentioning
confidence: 99%